THE INFLUENCE OF ORGANIZATIONAL CULTURE AND WORK COMPETENCE ON THE QUALITY OF HUMAN RESOURCES IN KLARI DISTRICT OFFICE EMPLOYEES - Nadya Fatma Intani; Asep Jamaludin; Nandang (PT. Berkah Digital Teknologi, 2025)
Purpose: To determine and analyze the partial and simultaneous effects of organizational culture and work competencies on the quality of human resources of employees at the Klari sub-district office. Research Methodology: This study applies a saturated/census sampling technique and utilizes quantitative methods with questionnaires as the data collection tool. Multiple linear regression analysis was used for data analysis. Results: Organizational culture partially affects the quality of human resources, work competence partially affects the quality of human resources, and organizational culture and work competence simultaneously affect the quality of human resources of Klari sub-district office employees. Limitations: The study was conducted only with employees of the Klari sub-district office, a relatively small population. Contribution: The findings of this study can be useful for improving the quality of human resources in the public sector, particularly in local government offices.